Pathophysiological Correlation between Cigarette Smoking and Amyotrophic Lateral Sclerosis - Spiro Menounos; Philip M. Hansbro; Ashish D. Diwan; Abhirup Das (NeuroSci, 2021)
Cigarette smoke (CS) has been consistently demonstrated to be an environmental risk factor for amyotrophic lateral sclerosis (ALS), although the molecular pathogenic mechanisms involved are yet to be elucidated. Here, we propose different mechanisms by which CS exposure can cause sporadic ALS pathogenesis. Oxidative stress and neuroinflammation are widely implicated in ALS pathogenesis, with blood–spinal cord barrier disruption also recognised to be involved in the disease process. In addition, immunometabolic, epigenetic and microbiome alterations have been implicated in ALS recently. Identification of the underlying pathophysiological mechanisms that underpin CS-associated ALS will drive future research to be conducted into new targets for treatment.